Canadian Hydropower in the Pacific Northwest. Issue 6 (January 2015) - Sivertson, Lorne
<x xml:space="preserve">Abstract</x> While the focus of this article is on one region of the world, the information, it is believed, should be of a wider interest. The issue has implications for other areas of the planet, including China, where meeting energy requirements is a major challenge.